(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
Issues of Patient Safety during and after COVID-19 crises came before the Delhi High Court for consideration on constitutional provisions and registration and regulation of online health service aggregators including medical practice and diagnostic services in a Public Interest Litigation and subsequently contempt petition for non compliance of High Court order. The petitioner alleged that despite the fact that the online aggregators are not registered as labs they are functioning all over the country and collecting lab samples and submitting test reports. One example has been cited of LSS Healthcare Pvt. Ltd. (1 mg Labs) to contend that the said organization is an online aggregator and is carrying out clinical tests and submitting reports which is contrary to law. The Ld. CGSC for the Union of India submitted that the matter pertains exclusively to an Entry in the State List of the Seventh Schedule of the Constitution. However, the Court was informed that the adequate statutory scheme is not yet available under the State List, for ‘registration of clinical establishments’. The extant laws deal only with regulation of Nursing Homes. This Research Paper discusses various issues related to Post COVID-19 Scenario, Role of ICMR, Role of State Govt., Role of High Court / Supreme Court, Role of NMC/ SMC, Telemedicine /Tele-consultation has been discussed in brief. This will help in understanding complexity of law and sensitivity of issues in view of patient safety, constitutional provisions, ethical and illegality issues involved by various stakeholders dealing with patient safety.